The Synergic Effect of Artemisia dracunculus (Tarragon) Extract and Aspirin (ASA) on Platelet Function - AH Hedaryan; M Hamidpour; AM Ayatolahi; M Allah bakhshian Farsiani (Institue of Medicinal Plants, ACECR, 2019)
Background: Coagulation activity of platelets plays an important role in thrombosis formation, Atherosclerotic plaque establishment and cardiovascular disorders. ASA are using as an anti platelet activity drug for patients with Coronary Artery Disease (CAD). Using of plant extraction as a complementary medicine for these patients (CAD) is mostly recommended by traditional medicine specialist. Objective: In this study we investigated platelet activity after treatment with extract of Artemisia dracunculus (Tarragon) and it's synergic with ASA treatment. Methods: After preparation of platelets from healthy volunteers, platelets confronted with desired concentrations (125-1000 µg/ml) of methanol extract of Artemisia dracunculus (tarragon) and (0.31-1.26 µg/ml) of (ASA) alone and in combination.  The platelet function such as adhesion, aggregation and protein release were assayed on treated platelets and controls. Results: Our results demonstrated that Tarragon extract significantly effective on adhesion, aggregation and protein release in comparison with healthy volunteers platelets (P≤0.001). The Tarragon extract also raised the anti-platelet activity of ASA on these platelets. Conclusion: Tarragon extract, either as single agent or combination with ASA, has been able to induce anti-platelet activity. Therefore, it would be suggested to use of the tarragon extract with or without common treatments, i.e. ASA, in treatments of cardiovascular disorders and patients with deep vein thrombosis.